Analisis Pengaruh Profitabilitas, Leverage Dan Ukuran Perusahaan Terhadap Financial Distress - Fauziah Arif Efendi; Dedi Fernanda; Khadijah Ath Thahirah (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This research was conducted with the aim of proving the effect of profitability, leverage, and company size on financial distress. The population in this study are all service companies in the tourism sub-sector, hotels and restaurants listed on the IDX in 2018-2021. The research method used is quantitative with a sampling technique using purposive sampling so that there are 28 companies with 4 years of observation. The data collection method used is documentation and the data used is secondary data from the company's annual financial reports. The data analysis technique is multiple linear regression using SPSS 25. The results of the study partially show that profitability as measured by return on assets has a positive effect on financial distress, leverage as measured by the debt to assets ratio has a negative effect on financial distress, and firm size as measured by the natural logarithm of assets has no effect on financial distress. While simultaneously the variables of profitability, leverage, and firm size have a significant effect on financial distress